Anti-CTGF/PD-1 bispecific antibody Y126S restrains desmoplastic and immunosuppressive microenvironment in pancreatic cancer - Wei Chen; Hai Huang; Wang Peng; Jingwen Liang; Shiru Chen; Yuchong Zhao; Mengdie Cao; Yilei Yang; Shuya Bai; Qiaodan Zhou; Jiamei Jiang; Yilin Gu; et al. (Journal for ImmunoTherapy of Cancer)
Background Pancreatic ductal adenocarcinoma (PDAC) is characterized by a desmoplastic and immunosuppressive tumor microenvironment (TME), limiting the efficacy of immune checkpoint inhibitors such as anti-programmed cell death 1 (PD-1).Methods This study aimed to evaluate the therapeutic potential of Y126S, a recombinant IgG1/IgG2 hybrid bispecific antibody (BsAb), in reshaping the immunotherapy-resistant TME in PDAC. Orthotopic PDAC and KPC (KrasLSL-G12D/+; Trp53LSL-R172H/+; Pdx1-Cre) mouse models were established and treated with Y126S, α-connective tissue growth factor (CTGF), α-PD-1, or a combination of α-CTGF and α-PD-1. TME remodeling, antibody distribution, and therapeutic efficacy were assessed using flow cytometry, immunohistochemical/Masson staining, atomic force microscopy, positron emission tomography (PET) imaging, distribution analysis, and other experimental techniques.Results Here, Y126S was characterized in vitro and its antitumor efficacy was evaluated and validated in orthotopic PDAC mice and KPC mouse models. Notably, Y126S significantly remodeled the TME and demonstrated superior tumor-specific accumulation compared with single α-PD-1 treatment, leading to markedly enhanced antitumor efficacy relative to its parental antibodies or their combination. Mechanistically, Y126S suppressed cancer-associated fibroblasts (CAFs) activation, reduced collagen deposition, and downregulated programmed cell death ligand 1 (PD-L1) expression on CAFs by targeting CTGF and enhanced the anti-PD-1-mediated reinvigoration of cytotoxic CD8+ T cells, thereby establishing a less desmoplastic and potent tumor-killing microenvironment.Conclusions Our findings highlight the potential of Y126S as a promising BsAb-based immunotherapy strategy for PDAC by remodeling the desmoplastic and immunosuppressive TME.